2008
DOI: 10.1002/lsm.20605
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of resistant tattoos using a new generation Q‐switched Nd:YAG laser: Influence of beam profile and spot size on clearance success

Abstract: Background and Objectives: Multiple treatments of resistant tattoos often result in fibrosis and visible textural changes that lessen response to subsequent treatments. The aim of this study is to evaluate the influence of beam profile and spot size on clearance rates and side effects in the setting of resistant tattoos. Study Design/Material and Methods: Thirty-six professional, black tattoos (32 patients) were treated unsuccessfully with a Q-switched Nd:YAG laser (MedLite TM C3, HoyaConBio Inc., Fremont, CA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…It is more related to the patient’s skin type, with darker skin being more prone regardless of the wavelength. The incidence is normally in the same order of magnitude as that of hypopigmentation, but can be as high as 25% after repeated removal attempts 14,15 …”
mentioning
confidence: 99%
“…It is more related to the patient’s skin type, with darker skin being more prone regardless of the wavelength. The incidence is normally in the same order of magnitude as that of hypopigmentation, but can be as high as 25% after repeated removal attempts 14,15 …”
mentioning
confidence: 99%
“…We found that under the present conditions, fluences of 0.7 to 1.6 J/cm 2 were effective in the removal of tattoos compared with fluences of 9.0 to 12.0 J/cm 2 commonly reported in the literature. [9][10][11] In addition, the tattoo removal process in the present case required shorter therapy sessions and spacing between sessions of 1 to 2 weeks compared with the 4 to 8 weeks needed in other laser treatments. 15 The present study should be considered initial, and there are some venues that should be further explored.…”
Section: Commentmentioning
confidence: 98%
“…A flat-top (or top-hat) profile is preferred to a Gaussian profile in order to ensure the skin surface temperature is homogenised, as is the temperature of the heated volume (8). This flat-top power profile gives a more homogeneous heating effect throughout the heated area, rather than a selective heating action.…”
Section: Top-hat Profilementioning
confidence: 99%